Sistem Pakar Diagnosa Penyakit Tanaman Bunga Kertas Zinnia Menggunakan Metode Certainty Factor - Nanik Triatmi; Mutaqin Akbar (Journal of Information System and Artificial Intelligence, 2021)
Paper flowers or Zinnia flowers are annual plants belonging to the Zinnia genus. This flower comes from Mexico, grows as an ornamental plant that is spread in various parts of the world, including in Indonesia. Zinnia paper flowers are very popular in Indonesia, this plant is often used for ornamental plants. However, in plant care sometimes ornamental plant farmers experience several obstacles due to diseases or plant pests that attack because there is still a lack of knowledge and handling about these plants. Because if the plants are not handled quickly it will make farmers suffer losses. The purpose of building an expert system for diagnosing zinnia paper flower plant diseases, with this expert system it can be more effective to assist farmers in dealing with diseases or pests that attack The inference process uses the certainty factor method, looks for symptom data and then selects parameters according to existing conditions, then processed with diagnostic results in the form of type of disease, percentage results, disease details and suggestions. Based on 18 symptoms and 5 types of disease, 25 system test data were obtained, 20 data results were appropriate and 5 data results did not match so that the average percentage result was 80%.